Electrochemical Performance of Graphene-Modulated Sulfur Composite Cathodes Using LiBH4 Electrolyte for All-Solid-State Li-S Battery - Tarun Patodia; Mukesh Kumar Gupta; Rini Singh; Takayuki Ichikawa; Ankur Jain; Balram Tripathi (Energies, 2021)
All-solid-state Li-S batteries (use of solid electrolyte LiBH4) were prepared using cathodes of a homogeneous mixture of graphene oxide (GO) and reduced graphene oxide (rGO) with sulfur (S) and solid electrolyte lithium borohydride (LiBH4), and their electrochemical performance was reported. The use of LiBH4 and its compatibility with Li metal permits the utilization of Li anode that improves the vitality of composite electrodes. The GO-S and rGO-S nanocomposites with different proportions have been synthesized. Their structural and morphological characterizations were performed by X-ray diffraction (XRD) and scanning electron microscopy (SEM), and the results are presented. The electrochemical performance was tested by galvanostatic charge-discharge measurements at a 0.1 C-rate. The results presented here demonstrate the successful implementation of GO-S composites in an all-solid-state battery.